O PERFIL EPIDEMIOLÓGICO DE INTERNAÇÕES POR INFARTO AGUDO DO MIOCÁRDIO NO ESTADO DO PARANÁ ENTRE 2016 E 2022 - Omairi, Alexandre (2023)
OBJECTIVE: To describe the epidemiological characteristics of hospitalizations for Acute Myocardial Infarction in the state of Paraná between the years 2016 and 2022. METHOD: The research adopts a quantitative and descriptive methodology, employing a retrospective approach with data obtained through the Department of Informatics of the Unified Health System (DataSUS). The analysis of epidemiological characteristics is based on variables such as CID-10 category, gender, age, and race, covering the period from 2016 to 2022 in the state of Paraná. RESULTS: Between 2016 and 2022 in the state of Paraná, a total of 56,420 hospitalizations for acute myocardial infarction were recorded in patients aged 20 to 80 and above. The predominantly affected age group was 60 to 69 years with 17,252 cases (30.5%). Patients between 50 and 59 years also showed significant numbers, totaling 14,082 hospitalizations (24.9%). Regarding gender, men were more frequently affected with 36,484 hospitalizations (64.6%). As for race, it was observed that the white population was the most affected, accounting for 41,921 hospitalizations (74.3%). CONCLUSION: Acute Myocardial Infarction (AMI) is a frequent cause of hospitalization in the Unified Health System, particularly prevalent among individuals aged 50 to 59. Additionally, there is a male and white population predominance. Therefore, it becomes essential to screen for AMI risk factors and raise awareness among the populations most affected by age groups.